Prospect Produksi Pra Sapih Anak Kambing Hasil Silang Kambing Pe Dengan Kambing Boer - Lalu Ahmad Zaenuri; Lukman HY; Oscar Yanuarianto (LPPM Universitas Mataram, 2018)
The study aims to evaluate the pre-weaning production prospectus kids of PE crossed with Boer buck. Twenty PE does were in the average 39.35 kg body weight and 3 in body condition score. Does were offered single feed sesbandia glandiflora leaves twice a day. All does were synchronized by 2 ml Capriglandin, inseminate fix time at 48-52 hours following Capriglandin injection. If the does were return to estrus following AI, then they were allowed natural mating. Data collected included gestation period, birth weight and average daily gain (ADG), tabulated and calculated for Mean±SD, interpreted and explained descriptively. The number of kid were 34 consisting of 6 singles male (SM), 12 single female (SF), 8 male twin (MT), 2 female twins (FT) and 6 male-female twins (MFT). Gestation period (days) were 152±0.47 and 152±2.00 for SM and MT. Shorten gestation period were noted for SF, FT and MFT (149±3.82; 150±3.94 and 147±2.94, respectively). The highest birth weight (kg) was SM (4.27±0.29) followed by SF (3.52±0.27), MFT (2.97±0.44), FT (2.73±0.23) and MT (2.71±0.54). The highest ADG (gr/day) occurred at 0-30 days was in MT (201.33 g/d) and the lowest was in FT (137.33 g/d). In conclusion, crossbreeding kid of PE VS Boer goat has a high prospectus as dual purpose stockbreeder